2018
DOI: 10.3791/57420
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive, High-throughput Determination of Sleep Duration in Rodents

Abstract: Traditionally, sleep is monitored by an electroencephalogram (EEG). EEG studies in rodents require surgical implantation of the electrodes followed by a long recovery period. To perform an EEG recording, the animal is connected to a receiver, creating an unnatural tether to the head-mount. EEG monitoring is time consuming, carries risk to the animal, and is not a completely natural setting for the measurement of sleep. Alternative methods to detect sleep, particularly in a high-throughput fashion, would greatl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Though mouse sleep can be measured using other noninvasive approaches, EF sensor recordings have the additional ability to simultaneously quantify other motor behaviors such as ventilation profiles in non-REM and REM sleep, grooming, locomotion, eating, and drinking using only a frequency-based features of a single voltage channel. 31 Other noninvasive movement-based methods to measure rodent sleep have been reported using video, [18][19][20]22,43 whole body plethysmography, 7,11 infrared beams, 19,44 pulse Doppler radar, 21 piezoelectric films, 10,24,[45][46][47] and actimetry. 48,49 Several of these approaches, namely video, infrared beams, and actimetry, cannot distinguish non-REM from REM sleep 18,19,22,[43][44][45][46][47][48][49] limiting their applications to when only sleep/wake discrimination is sufficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though mouse sleep can be measured using other noninvasive approaches, EF sensor recordings have the additional ability to simultaneously quantify other motor behaviors such as ventilation profiles in non-REM and REM sleep, grooming, locomotion, eating, and drinking using only a frequency-based features of a single voltage channel. 31 Other noninvasive movement-based methods to measure rodent sleep have been reported using video, [18][19][20]22,43 whole body plethysmography, 7,11 infrared beams, 19,44 pulse Doppler radar, 21 piezoelectric films, 10,24,[45][46][47] and actimetry. 48,49 Several of these approaches, namely video, infrared beams, and actimetry, cannot distinguish non-REM from REM sleep 18,19,22,[43][44][45][46][47][48][49] limiting their applications to when only sleep/wake discrimination is sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…31 Other noninvasive movement-based methods to measure rodent sleep have been reported using video, [18][19][20]22,43 whole body plethysmography, 7,11 infrared beams, 19,44 pulse Doppler radar, 21 piezoelectric films, 10,24,[45][46][47] and actimetry. 48,49 Several of these approaches, namely video, infrared beams, and actimetry, cannot distinguish non-REM from REM sleep 18,19,22,[43][44][45][46][47][48][49] limiting their applications to when only sleep/wake discrimination is sufficient. Of the published studies capable of noninvasively measuring 3state sleep architecture, the reported overall accuracies to EEG/EMG range from 84% to 91%, 10,11,20,21,24 .…”
Section: Discussionmentioning
confidence: 99%
“…At 60–77 days of age, we assessed sleep duration by means of the home-cage activity monitoring system (Comprehensive Laboratory Animal Monitoring System (CLAMS)) (Columbus Instruments, Columbus, OH, USA) as previously described [ 20 ]. Briefly, mice were singly housed in a standard mouse cage for the duration of the sleep assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Animals were separated into individual standard mouse cages and placed in the activity monitoring system (CLAMS) (Columbus Instruments, Columbus, OH, United States) for 72 h. To allow for habituation to the single housing and monitoring system, only the last 48 h-period was analyzed (Sare et al, 2018). Activity was recorded in 10 s epochs.…”
Section: Methodsmentioning
confidence: 99%